The plan : manage your time like a lazy genius - Adachi, Kendra (Convergent, 2024)
"Why do so-called life hacks leave us drowning in tasks, schedules, and unfulfilled expectations? In her straightforward, humorous style, author Kendra Adachi reveals why the problem is not you. Most time management systems prioritize optimization and greatness in service to an imagined future, but what if that's not your goal? What if you long for a book that helps you live wholeheartedly today? The PLAN is the answer. Using the memorable acronym "PLAN," you will learn to prepare, live, adjust, and notice like a Lazy Genius, all through the lens of what matters to you in your current season: Discover two beliefs that will change time management forever; Integrate your hormones, personality, and life stage into your planning process; Learn the Lighten the Load to-do list framework to help you get your stuff done; Use The PLAN Pyramid to help you visualize a balanced life; Experience freedom from the crushing pressure of greatness, potential, and hustle. Refreshingly compassionate and immediately practical, The PLAN is the book-and the framework-you've been waiting for"--